The Infinite-Valued Łukasiewicz Logic and Probability - Czelakowski, Janusz (Bulletin of the Section of Logic, 2017)
The paper concerns the algebraic structure of the set of cumulative distribution functions as well as the relationship between the resulting algebra and the infinite-valued Łukasiewicz algebra. The paper also discusses interrelations holding between the logical systems determined by the above algebras.